Performance and economic analysis of a reversed circular flow jet impingement bifacial PVT solar collector - Muhammad Amir Aziat Bin Ishak; Adnan Ibrahim; Kamarruzaman Sopian; Mohd Faizal Fauzan; Aqil Afham Rahmat; Nurul Jannah Yusaidi (International Journal of Renewable Energy Development, 2023)
As the world shifts towards a more sustainable future, solar energy has emerged as a preeminent and economically feasible alternative to traditional energy sources, gaining widespread adoption. This study presents a reversed circular flow jet impingement (RCFJI) which aims to improve the performance of a bifacial PVT collector. An indoor experiment using a solar simulator to assess the energy, exergy, and economic efficiency of a RCFJI bifacial PVT collector. The study was carried out using a solar irradiance ranging from 500-900W/m2 and a mass flow rate between 0.01-0.14 kg/s. Energy performance-wise, the highest photovoltaic efficiency achieved was 11.38% at solar irradiance of 500 W/m2, while the highest thermal efficiency achieved was 61.4% under 900 W/m2, both obtained at 0.14 kg/s mass flow rate. Regarding exergy performance, the highest photovoltaic exergy obtained was 47.27 W under 900 W/m2 at 0.14 kg/s, while the highest thermal exergy was 9.67 W at 900 W/m2 at 0.01 kg/s. Overall, higher solar irradiance is more desirable for energy and exergy performance. Meanwhile, economic point of view, lower solar irradiance is preferable. Based on the findings, the optimal mass flow rate was 0.06 kg/s.